2015
DOI: 10.1128/ec.00011-15
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Candida albicans Phosphoproteome

Abstract: dCandida albicans is an important human fungal pathogen in both immunocompetent and immunocompromised individuals. C. albicans regulation has been studied in many contexts, including morphological transitions, mating competence, biofilm formation, stress resistance, and cell wall synthesis. Analysis of kinase-and phosphatase-deficient mutants has made it clear that protein phosphorylation plays an important role in the regulation of these pathways. In this study, to further our understanding of phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
67
2
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(95 citation statements)
references
References 79 publications
16
67
2
10
Order By: Relevance
“…Since cbk1D/D does not form filaments, lysates from yeast phase cells were used for these experiments. Consistent with the extensive phosphorylation of Rgd3 apparent in the data set reported by Willger et al (2015), multiple species of Rgd3 with a wide range of isoelectric points are apparent in blots derived from WT cells ( Figure 7B). In contrast, Rgd3-GFP isolated from cbk1D/D cells shows a much less complex pattern, suggesting that significant changes in Rgd3 phosphorylation result from loss of Cbk1 activity.…”
Section: Cbk1 Interacts With Two Genes Related To Cell Polarity Throusupporting
confidence: 72%
See 3 more Smart Citations
“…Since cbk1D/D does not form filaments, lysates from yeast phase cells were used for these experiments. Consistent with the extensive phosphorylation of Rgd3 apparent in the data set reported by Willger et al (2015), multiple species of Rgd3 with a wide range of isoelectric points are apparent in blots derived from WT cells ( Figure 7B). In contrast, Rgd3-GFP isolated from cbk1D/D cells shows a much less complex pattern, suggesting that significant changes in Rgd3 phosphorylation result from loss of Cbk1 activity.…”
Section: Cbk1 Interacts With Two Genes Related To Cell Polarity Throusupporting
confidence: 72%
“…Rgd3 contains a large number of predicted protein kinase phosphorylation motifs and, consistent with that analysis, phosphoproteomics data recently reported by Willger et al (2015) indicate that Rgd3 contains a total of 27 phosphorylated serine or threonine residues. We wondered whether loss of Cbk1 function may affect the phosphorylation state of Rgd3.…”
Section: Cbk1 Interacts With Two Genes Related To Cell Polarity Throusupporting
confidence: 55%
See 2 more Smart Citations
“…Corresponding to this notion, ACE2 overexpression restored the sensitivity phenotypes of all mutants in the Cek1 pathway except in the cek1 mutant, indicating that Ace2 activation requires phosphorylation by Cek1 and that an increase in Ace2 levels obviates the necessity for Ace2 activation by upstream components. Ace2 was found to contain 18 phosphorylated residues (Willger et al ., ), which may be due to the action of Cek1 and other kinases, including Cst20 (discussed below). Previously, it was shown that ACE2 overexpression is able to suppress the sensitivity phenotypes of the pmt1 mutant (Cantero and Ernst, ), which probably is mediated by induced expression of PMT2/PMT4 genes.…”
Section: Discussionmentioning
confidence: 95%